Tyrosine 27 of the specificity polypeptide of EcoKI can be UV crosslinked to a bromodeoxyuridine-substituted DNA target sequence. - Chen, A; Powell, L; Dryden, D; Murray, N; Brown, T (1995)
The specificity (S) subunit of the restriction enzyme EcoKI imparts specificity for the sequence AAC(N6)GTGC. Substitution of thymine with bromodeoxyuridine in a 25 bp DNA duplex containing this sequence stimulated UV light-induced covalent crosslinking to the S subunit. Crosslinking occurred only at the residue complementary to the first adenine in the AAC sequence, demonstrating a close contact between the major groove at this sequence and the S subunit. Peptide sequencing of a proteolytically-digested, crosslinked complex identified tyrosine 27 in the S subunit as the site of crosslinking. This is consistent with the role of the N-terminal domain of the S subunit in recognizing the AAC sequence. Tyrosine 27 is conserved in the S subunits of the three type I enzymes that share the sequence AA in the trinucleotide component of their target sequence. This suggests that tyrosine 27 may make a similar DNA contact in these other enzymes.